Konsep & Kerangka Analisis Manajemen Strategis Dakwah - Affandy, Shofyan (STID Al Hadid Surabaya, 2025)
Disruptive forces have penetrated nearly all dimensions of life, triggering radical transformations in thinking patterns, work systems, and institutional structures. These shifts demand adaptive responses not only from individuals but also from social, commercial, and public institutions. Organizational adaptability to such environmental dynamics requires a robust set of concepts and responsive strategic analysis frameworks to sustain competitive advantage. In the context of da’wah organizations, there is a pressing need for a theoretical transformation of strategic management concepts that aligns with the distinct nature of the da’wah environment. This transformation should go beyond axiological concerns and encompass strategic and methodological dimensions. This study employs a qualitative-theoretical approach (basic research), using deductive analysis to synthesize conventional strategic management concepts with the essence and characteristics of Islamic da’wah. The outcome is a theoretical reconfiguration of strategic concepts and competitive advantage, alongside the development of an analytical framework tailored to the unique environment of da’wah organizations. Traditional da’wah approaches inherited from the past must evolve into a more strategic form of da’wah—one that is adaptive, innovative, competitive, and multidimensionally effective. Furthermore, competitive advantage must shift towards collaborative advantage, emphasizing mutualistic partnerships with the target audience (mad‘u). As a consequence, the conventional business-oriented SWOT analysis framework should be reinterpreted into a more holistic and optimistic SWOT framework that reflects the values and goals of da’wah.